UPAYA MENINGKATKAN KINERJA GURU MELALUI PENGGUNAAN ALAT PERAGA DENGAN PEMBELAJARAN LANGSUNG DI SDN 007 ROKAN IV KOTO - Syofian Daud (JURNAL PENDIDIKAN ROKANIA, 2018)
This study aims to determine whether the performance of teachers can be improved through the use of props with direct learning in SDN 007 Rokan IV Koto. The teacher who became the subject of research consists of 13 teachers. Characteristics of teachers have a heterogeneous motivation, but can not be said to use props intensively while doing the learning. From the description of data processing and discussion, it can be concluded that the performance of teachers is obtained in the first cycle of 63% with good category and in the second cycle increased to 76% with good category. Meaning that Activity Use props with direct learning can improve teacher performance in SDN 007 Rokan IV Koto said successful.